Judgments of learning (JOLs) selectively improve memory depending on the type of test - Myers, Sarah J.; Rhodes, Matthew G.; Hausman, Hannah E. (Memory & cognition, 2020)
JOL reactivity refers to the finding that making judgments of learning (JOLs) while studying material influences later memory for that material. Findings of JOL reactivity have been mixed, with some experiments reporting changes to memory when participants make JOLs and others finding no influence of JOLs. Soderstrom, Clark, Halamish, and Bjork ( Journal of Experimental Psychology: Learning, Memory, and Cognition, 41 (2), 553–558, 2015 ) proposed that JOL reactivity will only occur if the final test is sensitive to the same cues used to inform JOLs. The current study evaluated this account by manipulating the type of final test. In four experiments, participants studied mixed lists of related and unrelated word pairs and either made JOLs or did not make JOLs. Making JOLs generally enhanced memory for related word pairs when a cued-recall test was administered. However, during free recall, JOLs had no influence on memory for target information, likely because cue–target associations (which are used to inform JOLs) are less beneficial in the absence of cues. JOLs improved item recognition memory for words that were studied in related pairs, although the effect was small. Collectively, data from a meta-analysis of these experiments indicate that JOL reactivity depends on the type of final test, with reactivity most likely to occur when the final test is sensitive to the same cues used to inform JOLs. Future work should continue examining different tests and study materials in order to develop a comprehensive theory of JOL reactivity.